1997
DOI: 10.1159/000177999
|View full text |Cite
|
Sign up to set email alerts
|

Fasting during Ramadan Induces a Marked Increase in High-Density Lipoprotein Cholesterol and Decrease in Low-Density Lipoprotein Cholesterol

Abstract: We demonstrated for the first time in a Moroccan population that fasting during Ramadan, the ninth lunar month of the Muslims’ year, affected lipid and lipoprotein metabolism in a group of 32 healthy adult male volunteers. This investigation was conducted to study the changes in serum total cholesterol, triglycerides, cholesterol in high-density lipoprotein (HDL) and low-density lipoprotein (LDL), glucose, and body weight during Ramadan. The results showed a significant decrease (7.9%, p < 0.001) in serum tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
146
5
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 20 publications
12
146
5
3
Order By: Relevance
“…It was therefore with some surprise that weight gain was not observed in our patients post-Ramadan. This observation has however been well documented elsewhere (Husain et al, 1987;Finch et al, 1998;Adlouni et al, 1997Adlouni et al, , 1998Maislos et al, 1993Maislos et al, , 1998el Ati et al, 1995) and is believed due to an increase in fat oxidation during Ramadan, as an adaptive mechanism for body weight maintenance (el Ati et al, 1995). Another explanation offered is a reported reduced appetite observed in groups of fasting moslems in the UK, especially towards the end of the Ramadan period (Finch et al, 1998), but we were unable to document this in our subjects.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…It was therefore with some surprise that weight gain was not observed in our patients post-Ramadan. This observation has however been well documented elsewhere (Husain et al, 1987;Finch et al, 1998;Adlouni et al, 1997Adlouni et al, , 1998Maislos et al, 1993Maislos et al, , 1998el Ati et al, 1995) and is believed due to an increase in fat oxidation during Ramadan, as an adaptive mechanism for body weight maintenance (el Ati et al, 1995). Another explanation offered is a reported reduced appetite observed in groups of fasting moslems in the UK, especially towards the end of the Ramadan period (Finch et al, 1998), but we were unable to document this in our subjects.…”
Section: Discussionmentioning
confidence: 46%
“…Most of the reports (Frost & Pirani, 1987;Husain et al, 1987;Finch et al, 1998;Adlouni et al, 1997Adlouni et al, , 1998Maislos et al, 1993Maislos et al, , 1998el Ati et al, 1995) on the in¯uence of Ramadan fasting on blood lipid and lipoprotein levels have been on healthy volunteers. In studies performed on Ramadan fasting individuals, Frost and Pirani (1987) indicated that a signi®cant increase in caloric, fat, carbohydrate and protein intake during Ramadan resulted in a mean weight gain of about 2 kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of Indonesian people are Muslims, who are obliged to fast (total abstinence from food and drink) for as long as 14 h (from 0330 to 1730) each day for a month. Many studies have been conducted to evaluate the impact of Ramadan fasting on various aspects of health, including lipid metabolism (Fedail et al, 1982;El Arnoaty and Johnson, 1991;Adlouni et al, 1997), acute coronary heart disease and respiratory system (Temizhan et al, 1999;Ramadan and Barac-Nieto, 2000), water balance (Duncan et al, 1990;Schmahl and Metzler, 1991;Leiper et al, 2003;Basiri et al, 2004), dietary intake, endocrine function, serum fructosamine, and clinical, anthropometrical, and most biological parameters (Habbal et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Gharbi et al, 2003;Gustaviani et al, 2004;Kassab et al, 2004;Yucel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been only a few studies that examined the effect of the fast on basic homeostatic functions. [1][2][3] There have been several animal studies that have shown that hypertension can be caused or exacerbated by cycles of fasting and refeeding. [4][5][6][7] Initially, during the fast, there is a reduction in blood pressure.…”
Section: Introductionmentioning
confidence: 99%